2023
DOI: 10.3390/su15010876
|View full text |Cite
|
Sign up to set email alerts
|

Nano-Microbial Remediation of Polluted Soil: A Brief Insight

Abstract: The pollution of soil by heavy metals and organic pollutants has become a significant issue in recent decades. For the last few years, nanobiotechnology has been used to bio-remediate or reclaim soil contaminated with organic and inorganic pollutants. The removal of pollutants from industrial wastes is a major challenge. The utilization of nanomaterials is gaining popularity, which might be accredited to their enhanced physical, chemical, and mechanical qualities. The development of advanced nanobiotechnologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 131 publications
0
4
0
Order By: Relevance
“…The same principles of phytoremediation that nature utilizes are employed by microorganisms and plants to decrease organic and inorganic contaminants. 97 While previous studies have demonstrated the potential of nanophytoremediation of soil pollutants, 98 newer dimensions emphasize a deeper understanding of uptake mechanisms, enhanced plant–microbe interactions, tailored nanoparticle design, multicontaminant remediation, green synthesis, field-scale applications, risk assessment, and community engagement. These insights will contribute to the ongoing development of effective and sustainable nanophytoremediation strategies for diverse soil pollution challenges.…”
Section: Remediation Of Heavy Metals Using Nanotechnologymentioning
confidence: 99%
“…The same principles of phytoremediation that nature utilizes are employed by microorganisms and plants to decrease organic and inorganic contaminants. 97 While previous studies have demonstrated the potential of nanophytoremediation of soil pollutants, 98 newer dimensions emphasize a deeper understanding of uptake mechanisms, enhanced plant–microbe interactions, tailored nanoparticle design, multicontaminant remediation, green synthesis, field-scale applications, risk assessment, and community engagement. These insights will contribute to the ongoing development of effective and sustainable nanophytoremediation strategies for diverse soil pollution challenges.…”
Section: Remediation Of Heavy Metals Using Nanotechnologymentioning
confidence: 99%
“… 167 Furthermore, nanomaterials may show adverse effects on organisms found in soil, which may lead to negative implications in the seeking of remediation processes, aggravating soil conditions and affecting natural processes. 168 Nanoparticles used in water remediation processes (SDG 6) have been found to be effective in detecting and removing pollutants. Nevertheless, as with soil, natural conditions may affect the processes involved in water remediation.…”
Section: Challenges and Future Prospects Of Bmnps And Their Implement...mentioning
confidence: 99%
“…Metallic nanoparticles, specifically the ones with magnetic properties, are found to be unstable under acidic or alkaline conditions, which leads to the loss of their magnetic force and a reduced time of life. 168 This signifies a barrier in removing pollutants from contaminated water since the presence of, for example, heavy metals tends to reduce the pH of water. 169 In addition, the recuperation of nanomaterials in water treatment plants remains a significant challenge, as well as residue disposal after the degradation or adsorption of contaminants.…”
Section: Challenges and Future Prospects Of Bmnps And Their Implement...mentioning
confidence: 99%
“…Nano-materials have documented appreciable results in remediating polluted soils owing to their higher surface area, reactivity, and surface chemistry ( Khati et al., 2017 ; Baragaño et al., 2020 . Different types of nano-materials including zero-valent metals, metal oxide nanoparticles, carbon-based nano-materials, nano-composites, and nano-biosensors are used around the globe to remediate polluted soils ( Aliyari et al., 2023 ). The nano-materials serve as electron donors in the microbial reduction process and they promote the reduction of toxic metals.…”
Section: Modern Approaches Used To Remediate Hms Contaminated Soilsmentioning
confidence: 99%